Antipredator Behaviour of Limnonectes blythii (Boulenger, 1920) (Anura: Dicroglossidae) from Kedah, Peninsular Malaysia - Shahrudin, Shahriza (International Journal of Zoology, 2016)
The frog Limnonectes blythii was collected at different locations in Kedah, Peninsular Malaysia, three from Sungai Sedim Recreational Forest, two from Bukit Hijau Recreational Forest, and two from Ulu Paip Recreational Forest. Nine antipredator mechanisms were displayed by this species, including fleeing, hiding among leaf litter, diving into water, bladder discharge, defensive call, feigning death, crouching, inflating the body, and body-raising. The two latter actions were accompanied by a defensive call. These observations document for the first time antipredator behaviour in L. blythii.